Genetic variation and phylogenetic relationships among Rehmannia (Scrophulariaceae) species as revealed by a novel set of single-copy nuclear gene markers. (June 2016) - Huang, Jing; Zeng, Shu-Yun; Zhao, Jian-Hua; Han, Kai; Li, Jianfang; Li, Zhonghu; Liu, Zhan-Lin
Abstract: Single-copy nuclear genes (SCNGs) are effective tools for phylogenetic analysis in plants. In this study, genetic variation and interspecific relationships in the genus Rehmannia were investigated by a novel set of SCNG markers. In total, 12 pairs of primers were successfully amplified and sequenced in six Rehmannia species after screening 258 candidate genes from the transcriptome datasets of Rehmannia glutinosa . The moderate to high level of nucleotide polymorphisms were identified in these SCNG markers, and nucleotide diversity ( π ) per locus ranged from 0.00498 to 0.01100, with 6–10 haplotypes. R. chingii and R. piasezkii exhibited a high level of genetic variation, while R. glutinosa and R. solanifolia had no genetic diversity. Phylogenetic analyses suggested that R. glutinosa - R. solanifolia, R. elata - R. piasezkii should be classified as one species, respectively. Molecular dating supported the rapid speciation of Rehmannia in Pleistocene. The single-copy DNA markers developed here would be also helpful for the study on the process of speciation and the population dynamic history of Rehmannia . Highlights: We firstly developed 12 single-copy nuclear markers using transcriptome data in Rehmannia. Genetic diversity and phylogenetic relationships among the six species of Rehmannia were examined. The species tree indicated that the genus was involved in rapidly speciation in Pleistocene.